Emerging Therapeutic Strategies for Targeting Chronic Myeloid Leukemia Stem Cells - Ahmad Hamad; Zeyad Sahli; Maya El Sabban; Maha Mouteirik; Rihab Nasr (Stem Cells International)
Chronic myeloid leukemia (CML) is a clonal myeloproliferative disorder. Current targeted therapies designed to inhibit the tyrosine kinase activity of the BCR-ABL oncoprotein have made a significant breakthrough in the treatment of CML patients. However, CML remains a chronic disease that a patient must manage for life. Although tyrosine kinase inhibitors (TKI) therapy has completely transformed the prognosis of CML, it has made the therapeutic management more complex. The interruption of TKI treatment results in early disease progression because it does not eliminate quiescent CML stem cells which remain a potential reservoir for disease relapse. This highlights the need to develop new therapeutic strategies for CML to achieve a permanent cure, and to allow TKI interruption. This review summarizes recent research done on alternative targeted therapies with a particular focus on some important signaling pathways (such as Alox5, Hedgehog, Wnt/b-catenin, autophagy, and PML) that have the potential to target CML stem cells and potentially provide cure for CML.